ScreeningEffectiveness of The Extract of Sambiloto (Andrographis paniculata), Serai (Cymbopogon citrates) and Meniran (Phyllanthus niruri L.) as Dengue AntiviralIn Vitro - Sarah Luthfiani; Ratih Dewi Yudhani; Leli Saptawati (Nexus Biomedika, 2016)
Introduction: Dengue virus infection isone of the emergency infectious diseases in the world. Morbidity and mortality of dengue fever in Indonesia is relatively high.There is no specific therapy for dengue infection. The main treatment principle of dengue infection is supportive therapy such as replacement of body fluids. Indonesia has natural product which can be potential as an antiviral for dengue therapy, such as sambiloto (Andrographis paniculata), serai (Cymbopogon citrates) and meniran (Phyllanthus niruri L.). The aim of this research is to determine the effectiveness of the extract of sambiloto (Andrographis paniculata), serai (Cymbopogon citrates) and meniran (Phyllanthus niruri L.) as dengue antiviral in vitro. Methods:This study was a laboratory experimental research using dengue virus serotype 2 strain New guinea C (DENV2 NGC) which was infected into Huh-7 cell line as the subject of the research. This researchwas conducted in 2 parts. First ,inhibition test of the extract against DENV2 was assessed by the percentage of infectivity with Focus Forming Unit assay method . Second ,toxicity test of the extracts in HuH - 7 cells was assessed by the percentage of viability by MTT assay method. Effective herbs extract as a dengue antiviral was an extract that had average percentage of infectivity20% and average percentage of viability > 50%. Results: The extracts of sambiloto, serai, and meniranhad average percentage of infectivity: 53.8%; 114.4%; and 51.9%respectively. While the average percentage of viability were: 105.9%; 95.7%; and 98.6%respectively. Conclusion: The extracts of sambiloto (Andrographis paniculata), serai (Cymbopogon citrates), and meniran (Phyllanthus niruri L.) were not effective as dengue antiviral in vitro. Keywords: Andrographis paniculata, Cymbopogon citrates, Phyllanthus niruri L., DENV2 NGC,HuH-7.